Synthesis of model DNA and their application as substrates of nucleotide excision repair - Evdokimov, A.N.; Tsidulko, A.Yu.; Petruseva, I.O.; Koroleva, L.S.; Serpokrylova, I.Yu.; Silnikov, V.N.; Lavrik, O.I. (Вiopolymers and Cell, 2012)
Aim. Nucleotide excision repair (NER) is DNA repair system responsible to remove bulky lesions from DNA. These lesions appear in DNA as consequence of UV-light irradiation or environmental stress. Study of NER is extremely important to improve action of chemotherapeutic drugs. Methods. In vitro NER-assay and photoaffinity modification were used. Results. Long linear DNA analogs mimicking NER substrates have been synthesized. DNA analogs are 137-mer duplexes containing in their internal positions nucleotides with bulky substitutes imitating lesions with fluorochloroazidopyridyl and fluorescein groups introduced using spacer fragments at the 4N and 5C positions of dCMP and dUMP (Fap-dC- and Flu-dU-DNA) and DNA containing a (+)-cis-stereoisomer of benzo[a]pyrene-N2-deoxyguanosine (BP-dG-DNA). The interaction of the modified DNA duplexes with the proteins of NER-competent HeLa extract was investigated. The substrate properties of the model DNA in the reaction ofspecific excision were shown to vary in the row Fap-dC-DNA << Flu-dU-DNA < BP-dG-DNA. Conclusions. In vitro assay show that DNA analogs represent an interesting tool for the estimation of cellular repair activities. The developed approach should be of general use forthe incorporation of NER-sensitive distortions into model DNA and seems to be very promising for repair mechanism studies. Keywords: nucleotide excision repair, model bulky substituted DNA substrates.